Long- and short-term determinants of party preferences: Inter-generational differences in Western and East Central Europe - Walczak, Agnieszka; van der Brug, Wouter; de Vries, Catherine (Elsevier, 2012)
In this paper we study differences between generations in the degree to which long-term and short-term factors affect party preferences in established and consolidating European democracies. Scholarly literature has shown that younger cohorts in Western Europe are less likely to be guided by social class, religion and left/right than older cohorts. Little is known, however, about the extent to which such differences exist for the effects of short-term factors. Similarly, inter-generational differences in the effects of long- and short-term factors in post-communist countries have remained largely unexplored. Based on the European Election Study 2009, we show differences between generations that are compatible with de-alignment of younger generations along traditional cleavages. Yet, we also see an increased importance of attitudes towards immigration among the younger generations, which could signal a form of re-alignment.
Keywords: 59 Ciencia Política; ODS 10 - Reducción de las desigualdades